Administrative-Contractual Legal Relations with the Participation of the Internal Affairs’ Bodies in Administrative-Tort Sphere - A. I. Popov (Сибирское юридическое обозрение, 2018)
The article examines the problems of application of administrative-contractual legal relations in the activities of internal affairs’ bodies. It is proved that for participation in the administrative-contractual legal relations of the organs of internal affairs should have relevant expertise. The conclusion about the presence of activities of internal affairs’ bodies and public-service administrative-contractual legal relations, international administrative-contractual legal relations, coordination of administrative-contractual legal relations, administrative-contractual legal relations in the sphere of science and education and competency of administrativecontractual legal relations. Agreement in the administrative-tort industry with the participation of the internal affairs bodies should be recognized competency administrative-contractual legal relations, the content of which are the rights and obligations of the parties for the transfer of the powers for drawing up protocols on administrative offenses, responsibility for which is stipulated by the legislation of constituent entities. Analysis of administrativecontractual legal relations in administrative-tort field allows to conclude that the administrative and contractual regulation is an essential element of administrative activity of internal affairs bodies.